IMPLEMENTASI HOME LABORATORY TOPIK PERPINDAHAN KALOR UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS SISWA PADA MASA PANDEMI - Darma Okta Filujeng; Martini Martini; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The learning process in online classes during the pandemic rarely comes to practice, this can be overcome with a Home Laboratory practicum. Knowing the effect of implementing a Home Laboratory on the topic of heat transfer on the science process skills of SMP Negeri 60 Surabaya students during the covid 19 pandemic is the purpose of this research. Quasi experimental was used as the design and subjects of this study were students of class VII-A, VII-B, and VII-C of SMP Negeri 60 Surabaya for the academic year 2020/2021. The sample selection using random sampling technique or random selection of as many as twenty students. The instruments used are test and non-test with quantitative descriptive methods. The tests are in the form of pretest and posttest with multiple choice reasons, while the non-test is Home Laboratory performance assessment and student worksheet assessment. The data collection technique used a written test in the form of reasoned multiple-choice questions, the results were analyzed through percentages and then projected on improving science process skills. The interpretation criteria of the results of the analysis of each aspect of the science process skills of each student experienced an increase from the pretest. The average value of the performance score in each Home Laboratory practicum is said to exceed the KKM, which is 91.6. Overall, the results of the research on the implementation of the Home Laboratory practicum on the topic of heat transfer during the pandemic at SMP Negeri 60 Surabaya is said to be influential in training students' science process skills.